Kids Talk about Bravery - Carrie Finn (Minneapolis, MN, United States Picture Window Books, 2006)
I have my own room and sometimes I'm afraid at night. What can I do so that I don t get scared? Kind Kendra has some fearless advice on how to be brave."
Keywords: Read Aloud Non Fiction -- Read Aloud Non Fiction